IDDF2022-ABS-0174 The optimal cut-off values of serum ceruloplasmin and urinary copper in the diagnosis of wilson disease in CHB patients. (2nd September 2022) - Pang, Jiahui; Chen, Shuru; Yu, Meng; Wang, Heping; Zeng, Yingfu; Chong, Yutian; Gong, Jiao; Gan, Weiqiang; Li, Xinhua
Abstract : Background: The abnormality of serum ceruloplasmin (CP) and urinary copper in chronic hepatitis B (CHB) patients often confuses us whether they have concomitant Wilson disease (WD). Few studies have reported chronic hepatitis B (CHB) patients accompanied by Wilson disease (WD). We aimed to promote an understanding of clinical characteristics of patients with concurrent CHB and WD, and further identify such patients through screening appropriate parameters. Methods: A total of 35 patients with a concurrent diagnosis of CHB and WD were identified from January 2011 to December 2021. We enrolled 127 CHB patients but without WD from January 2016 to December 2021 as the control group. A propensity score matching was conducted to reduce the confounding. Receiver operating characteristic (ROC) curves were used to determine the optimal cut-off point of CP, 24-hour urinary copper and the combination of these two parameters. Results: In 26 patients (74.3%) with concurrent CHB and WD, the diagnosis of WD was delayed significantly more than that of CHB. The median interval time between the diagnosis of CHB and WD was 10 years (0–40). Twenty-two (62.9%) patients had cirrhosis at the time of the diagnosis of WD. Twenty-four (68.6%) of 35 patients developed liver failure. In diagnosing concomitant CHB and Wilson disease, the optimal cut-off value of serum CP is 0.1 g/L (sensitivity 74%, specificity 84%), and that of 24-hour urinary copper is 170 µg/24h (sensitivity 76%, specificity 100%). The combination of CP and 24-hour urinary copper got the highest area under curve (AUC) of 0.94 (95%CI, 0.894–0.987), followed by the 24-hour urinary (AUC = 0.864, 95%CI: 0.777–0.926) and serum CP (AUC = 0.838, 95%CI: 0.747–0.906). (IDDF2022-ABS-0174 Figure 1) Conclusions: Patients with CHB whose CP is below 0.1 g/L or 24-hour urinary copper is above 170 µg/24h are strongly recommended to undergo more tests to screen for WD.